Dynamical aspects of hardwood impregnation - Costanza, Vicente (2000)
The phenomenon of axial liquid penetration in hardwoods is modeled through two different mechanisms: in one of them the driving force is taken to be the empty space that remains unfilled inside the material; in the other one, it is the pressure differential between the interior of the material and its liquid environment. The equations obtained show an increase of liquid retention exponentially approaching an asymptote, which agrees with experimental results. By combining them with existing models for liquid permeability, an equation is obtained for predicting retention as a function of wood ultrastructure for a given liquid under fixed conditions